HUBUNGAN ANTARA PERSEPSI PASIEN RAWAT INAP TENTANG KUALITAS PELAYANAN KESEHATAN DENGAN CITRA RUMAH SAKIT UMUM PROVINSI NUSA TENGGARA BARAT - Sakti, Pandu Tridana; Syamsun, Arfi; Ekawanti, Ardiana (Faculty of Medicine Universitas Mataram, 2014)
Background: The hospital is a central care facility that is important as a central referral point for the lower care centers. Therefore, the hospital is required to provide adequate facilities and infrastructures, good quality and equity for all patients. The 2011 annual report of Provincial General Hospital West Nusa Tenggara indicated that the quality of health services in this hospital was low. It was felt necessary to undergo a research study to find out the inpatients perception of health care. Methods: A cross-sectional study was performed using stratified random sampling. The participants chosen were all inpatients of the Provincial General Hospital West Nusa Tenggara. A sample of inpatients was thus obtained of which questionnaires were usable for data analysis. A validity and reliability tested self administered questionnaire was used. Data was analysed with descriptive analysis, bivariate analysis using spearman method, and multivariate analysis using multiple linear regression to determine the effect on the health care quality toward hospital’s image. Results: Multivariate analysis showed that variables of health care quality (medical service, nurses, administration, supporting examination, pharmaceutical, nutritional, and physical facilities) significantly effected the image of the hospital. Based on the results of anova test, p value obtained was 0.000. Adjusted R2 value obtained was 0.966, indicating that the equation was good discrimination. Conclusion: There is a relationship between the quality of medical service, nursing, administration, supporting examination, pharmaceutical, nutritional, and physical facilities and the image of the Hospital. Keywords: Perception, Inpatients, Health Care Quality, Image, Hospital.